Orbital transitions: insight into energy transfer through an antenna for an organo-lanthanide complex. Issue 82 (29th September 2021) - Thor, Waygen; Zhang, Yonghong; Wong, Ka-Leung; Tanner, Peter A.
Abstract : Including experimental work, WFT and DFT calculations employing a range of functionals were performed for two lanthanide complexes to investigate, in different phases, the frontier orbitals and the orbital transitions between singlet states. Abstract : Supported by experimental work, wavefunction theory (WFT) calculations and density functional theory (DFT) calculations employing a range of functionals have been performed for two lanthanide complexes to investigate, in gas and solution phases, the representations of frontier orbitals and the orbital transitions between singlet states. The orbital transitions calculated using CASSCF/NEVTP2 served as reference. Functionals with a higher proportion of Hartree–Fock exchange gave better agreement with WFT. The choice of functional is therefore important for understanding the nature of orbital transitions and this is especially relevant in formulating antenna-metal ion energy transfer (ET) mechanisms.